Integrated management of solanum maurtianum in the highveld of Gauteng, South - Mtetwa, Sanele (My University, 2019)
Solanum mauritianum (Solanaceae) Scop., bugweed, is one of the most problematic invasive alien species in South Africa. Two biocontrol agents, a sap sucker Gargaphia decoris Drake (Tingidae) and a flower-feeder Anthonomus santacruzi Hustache (Anthonomini) have been released against the weed in KwaZulu-Natal. The damage of the agents to S. mauritianum is considered insufficient and the agents have not provided successful control of the weed since their release. Predicted limitations of establishment are mainly from predation for G. decoris and climate unsuitability for A. santacruzi. The efficacy of the two biocontrol agents on the Highveld is unknown. An alternative to biocontrol, the conventional methods of cutting and treating trees with herbicides are very expensive and labour-intensive, and if not properly implemented, they may allow resprouting to occur. Solanum mauritianum is reportedly easily killed by cutting followed by a herbicide treatment but the influence of stem diameter, cutting height, multiple stems and the timing of cutting had not been thoroughly evaluated, and had not yet been assessed in Gauteng. The aim of this study was to investigate the feasibility of biocontrol, and integrated control of S. mauritianum in the Highveld. Biocontrol experiments were conducted at the Wits nursery and Egoli Gas (shady site) in Johannesburg, and at Gerotek (sunny site) in Pretoria. Solanum mauritianum trees were exposed to G. decoris only, A. santacruzi only or G. decoris and A. santacruzi together. The biocontrol agents were either released on bagged/unbagged and ant-tack protected/unprotected trees. Ant-tack is a sticky compound applied on tree stems to deter insect predators. The releases were done in summer to increase the chances of agent survival. The numbers of surviving insects were counted on a monthly basis in order to assess their establishment. Integrated control experiments were conducted at Egoli Gas, Gerotek and two additional sites in Johannesburg, namely Parktown and Houghton. Solanum mauritianum trees that were already growing at these sites were either cut or cut and treated with the herbicide Hatchet, in spring and autumn, and also at different cutting heights. In addition, multistemmed trees in Parktown were cut and treated with herbicide to test the effect of the number of stems on the plant’s response to cutting. Monthly assessments of dead or live stumps were taken in each site. The results showed that none of the biocontrol agents in any treatment and at any site (including sun versus shade) were able to survive and establish viable populations. The predator exclusion techniques were successful at keeping ants and other insect predators off the protected trees but did not have an effect on the survival and establishment of the biocontrol agents. Anthonomus santacruzi’s failure to establish was attributed mainly to the lack of flowers on all experimental trees during the entire study. The low numbers of G. decoris released may have also influenced their survival. Nonetheless, the results suggest that the two biocontrol agents are not suitable for biocontrol of S. mauritianum in the Highveld. For the manual control trial, the highest mortality of trees was observed on those that were cut close to ground-level and treated with Hatchet. Cutting low and not applying Hatchet was not effective at killing S. mauritianum and resulted in a high percentage of resprouted stumps. The cut and herbicide treatment was much more effective in killing the trees than cut without herbicide treatment. The results also showed that stem diameter size, the number of cut stems per tree and the cutting season did not have a significant effect on stump survival. However, an increase in cutting height increased the percentage of resprouting stumps, especially on trees with thicker stems. Overall, future studies should focus on releasing A. santacruzi in warmer and more humid conditions, and only when the trees are flowering. Secondly future research should investigate releasing high numbers of G. decoris in the field to increase its chances of establishment. It is clear that cutting low and immediately treating stumps with Hatchet is the most effective method for killing S. mauritianum trees on the Highveld. However, challenges can be expected in cases where obstacles such as rocks and logs make it difficult to cut low and ultimately higher cuts may result in resprouting.
Masters dissertation University of the Witwatersrand School of Animal, Plant and Environmental Sciences May 2019